Development of a 3D bio-printer using CoreXY mechanism and syringe-based extrusion - Chin Fhong Soon; Mohammad Faez Ramilan; Dirman Hanafi; Wan Nurshazwani Wan Zakaria; Safinaz Mohd Khialdin; Hazlita Isa; Kian Sek Tee (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
3D Bio-printer is said to have potential in the applications of medical studies and tissue engineering. A 3D Bio-printer could be used to print the artificial organs for organs transplant and cell tissue culture for generating new cell tissue. It could help in future medical and biological research. This paper presents the development process, i.e. working principle of Fused Deposition Modelling (FDM), mechanical, electrical and related applied software, of a 3D Bio-printer using syringe-based extruder and Core XY mechanism. Up to date, FDM is a popular technique because it is easily implemented, precise and accurate. The printed product revealed high repeativity, where (sample mean, sample standard deviation) is (  mm. The procedure could help future customized 3D Bio-printer.